Semiotics in Qur'anic Interpretation: The Application of Semiotic Theory in the Tafsir of Jalalain, Ibn Kathir, and Al-Tabari on QS. An-Nur Verse 35 - Suhemi, Emi (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2024)
This study investigates methods of Qur'anic interpretation through a linguistic approach, with a focus on semantics and semiotics—both of which are essential for mufassirs (Qur'anic interpreters) in understanding Arabic. The primary objective is to explore how semiotic concepts are applied in interpreting the word نُور (Nuur, meaning